PRECONDITIONS FOR HARMONIZATION OF ACCOUNTING SYSTEMS OF RUSSIA AND CHINA - M.A. Amurskaya; R.I. Amirova; S.V. Gus`kov (Scientific Journal of Pedagogy and Economics, 2021)
This work provides a detailed review of the basic prerequisites and difficulties in the convergence of the Russian and Chinese accounting systems on the basis of IFRS. Purpose.The purpose of this article is to substantiate the possibility of convergence of the Russian and Chinese national accounting systems, both from theoretical and practical points of view. Methodology. The systematization of information about the analyzed objects was carried out by comparing the peculiarities of economical and historical development of Russia and China, and the characteristics of national ethics in the above-mentioned countries. Additional data were collected by analyzing the solutions for the financial statements at Russian-Chinese joint ventures, as well as by referring to the works of Russian and Chinese leading economists. Results. The author suggests a “club convergence” as a path to harmonize the accounting systems of the two countriessince this way takes into consideration the historical and cultural background of the national accounting systems of Russia and China. Conclusions.The research has revealedthat there exist a number of basic prerequisites for developing the regional convergence concept withinthe Russian and Chinese accounting systems. Such harmonization of national accounting systems will contribute to the developing of the methodological apparatus for comparing the main elements of accounting at joint Russian-Chinese enterprises, as well as to the successful implementation ofjoint investment projects in the energy sector, military-industrial complex, and the construction of large-scale infrastructure facilities, thus generally strengthening the trade cooperation between the two countries. The conclusions and recommendations made bythe author are used in training programs of the Russian-Chinese export center.